Effect of the addition of microcapsules with avocado peel extract and nisin on the quality of ground beef - Calderón‐Oliver, Mariel (Food Sci Nutr, 2020)
This study evaluated the incorporation of microcapsules containing nisin and avocado peel extract on the shelf life of ground beef. Ten treatments were studied and divided into two groups: one packaged under vacuum and the other in permeable packaging. Each group contained: (a) control, (b) extract, (c) nisin, (d) empty microcapsules (only wall microcapsule system), and (e) microcapsules with extract and nisin. The samples containing the microcapsules presented lower bacterial growth and less oxidation. On day 10, the vacuum‐packaged samples with microencapsulated preservative presented a reduction in the oxidation of proteins of approximately 45%, of 30% in the growth of mesophiles, and of 38% in the growth of coliforms, as well as a reduction in the changes in the pH and ɑ (W) that occur during storage, compared with the permeable control. The combination of microcapsules with vacuum packaging reduced the physicochemical and microbiological changes that occur in the controls.